The Effect of Ethnoscience Learning on the Development of Students' Cognitive and Affective Aspects in Junior High School - Hikmawati; I Wayan Suastra; Ketut Suma; A A Istri Agung Rai Sudiatmika; Endang Puji Astuti (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to examine the influence of ethnoscience learning on the development of students' cognitive and affective aspects. This quasi-experimental research uses a pre-test post-test non-equivalent control group design. This research was carried out in the odd semester of the 2022/2023 academic year. The population of this study was 320 class VII students at MTsN 1 Mataram, with a sample size of 34 people in the experimental class and 34 people in the control class. Data was obtained from test instruments for the "cognitive" aspect in the form of essays and questionnaire instruments for the "affective" aspect in the form of attitude statements. The statistical test used in this research is one-way MANCOVA with one covariate. The results of the research show that there is a significant difference in the influence of using ethnoscience learning on cognitive and affective learning simultaneously or together after controlling for students' initial abilities. The cognitive and affective scores of students in classes that use ethnoscience learning are higher than those in conventional classes. The conclusion of this research is that ethnoscience learning has a positive effect on the cognitive and affective aspects of junior high school students at MTsN 1 Mataram.